The Effect of Profitability, Firm Size, and Investment Opportunity Set (IOS) on the Earnings Quality - Pandaya; Anggita Mariska; Imam Suprapta (Kusuma Negara Business School, 2021)
The existence of profit management practices done by some large categorized companies tend to have a high profit but not yet be assured the resulting earning has good quality or not. The research was conducted to find empirical evidence of the influence of profitability, firm size and Investment Opportunity Set (IOS) on the quality of profit at the manufacturing companies of the food and beverage sub-sector listed at IDX from 2013 to 2018. In this study were secondary data originating from the annual report of the company's sub-sector and beverage-listed manufacturing companies in the year 2013-2018. Samples used as many as 11 companies. Data is processed with Eviews version 10 software. The results showed that profitability has a probability value of 0.5209 > 0.05 with a value of t-count -0.646268 < t-table 1.89458 and firm size has a probability value of 0.6905> 0.05 with -0.400462 <1.89458, so that it can damage profitability and company size has no effect on earning quality. Meanwhile, the Investment Opportunity Set (IOS) has a probability value of 0.0037 <0.05 with a value of t - count 3.044327> t - tab el 1.89458, which means that IOS has a positive and significant effect on earning quality.